Not every classroom lifts you up: school academic emphasis, teacher encouragement and motivation, and student constraints in reading achievement—a multilevel latent profile analysis - Turan, Selçuk (Frontiers in Psychology, 2026)
IntroductionThis study aims to identify latent profiles that emphasize academic success and examine how these profiles affect the interaction between classroom reading instruction, classroom climate, and student reading achievement.MethodsEmploying multilevel latent profile analysis combined with a cross-level moderation approach, the study used PIRLS 2021 data from 6,032 students across 192 schools in Türkiye.ResultsThe findings revealed two school profiles as perceived by teachers, one with a low emphasis on academic achievement and the other with a high emphasis. More specifically, in schools where teachers perceived a stronger focus on academic success, their encouragement and motivation efforts were more linked to higher student reading achievement. In contrast, in schools with a low emphasis on academic success, classroom instruction limited by student attributes negatively affected reading achievement; however, this association remained consistent across both profiles, indicating that school emphasis did not moderate this relationship.DiscussionThis study contributes theoretically by extending the School Effectiveness framework to show that school academic culture shapes the impact of classroom practices. The findings refine this framework by illustrating that instructional effects differ across schools with varying levels of academic emphasis. These results underscore the need for policies and leadership practices that cultivate strong academic cultures to enhance the effectiveness of classroom instruction.